Later-Life Mortality and Longevity in Late-18th and 19th-Century Cohorts. Where Are We Now, and Where Are We Heading? - Rich J. Mourits (Historical Life Course Studies)
The limits to human lifespan are a widely discussed topic. Yet, later-life mortality and longevity are generally studied from a genetic perspective, while the social dimension has received less attention. This paper gives a systematic overview of trends in later-life mortality and longevity for cohorts that were born in the late 18th and 19th century, and shows that the average population and the top survivors from cohorts born between 1800 and 1850 were already growing older. These improvements in human survival were similar for both of the sexes among the top survivors, whereas gender equality in the life expectancy at age 50 grew rapidly in cohorts born after 1880. Differences between populations were determined by the disease environment, availability of food, and local diets, while lifestyles and social support from spouses and kin affected later-life expectancy and longevity within these populations. These findings have major implications on how we view the demographic and epidemiological transition, and forces us to reconsider existing explanations for improvements in survival during the 19th century. However, in order to find out the determinants of later-life mortality, external validity of results, blind spots due to missing data, and familial clustering need to be studied more thoroughly.